MODERATING EFFECTS OF CONFORMITY CONSUMPTION AND CELEBRITY WORSHIP ON BUYER'S REMORSE SBT K-POP TWITTER - Amellia, Fitri Rizky; Usman, Usman (Institut Teknologi dan Bisnis Asia Malang, 2024)
This study investigates the effects of the Fear Of Missing Out (FOMO) and Impulsive buying constructs on buyer's remorse, employing moderating variables such as conformity consumption and Celebrity Worship among users of SBT K-pop (sell-buy-trade) accounts on Twitter. The research utilizes data from 201 samples collected through questionnaires distributed via various social media platforms, including Twitter, Line, and WhatsApp. The study demonstrates that the constructs of Conformity Consumption and Celebrity Worship can serve as moderators in the prediction model of SBT K-pop buyers' remorse on Twitter. The relationships between these constructs were analyzed using the Smart PLS program with bootstrapping techniques.